Information Ethics In The Qur'an: A Thematic Study Of Trust And Honesty In Facing Hoaxes - Nur Azizah Riska Ayu Astiani Mahmudah; Rifqatul Husna (International Journal of Science and Environment (IJSE), 2025)
The rapid development of information technology has drastically changed the way humans communicate. In this digital era, people can easily obtain information and disseminate it without proper verification, which can increase the potential for the spread of hoaxes. This phenomenon requires us to use good ethics in information and communication, especially regarding the values of trustworthiness and honesty. This study aims to examine the concept of trustworthiness and honesty in more depth through a thematic approach by referring to M. Quraish Shihab's Tafsir Al-Misbah. This study uses a qualitative method using a thematic interpretation approach (Maudhui'i), namely by collecting and analyzing verses related to the values of trustworthiness and honesty. From the results of this study, we obtain how the concept of trustworthiness and honesty in conveying information based on the Qur'an, and how the Qur'an provides guidance in dealing with hoaxes. This study explains more specifically by combining the concept of trustworthiness and honesty in dealing with hoaxes with a thematic interpretation approach.